Use Of Educational Technologies In Teaching The Subject "Static Exact Steel Structures And Their Calculation Methods" - O.M. Egamberdiyev; A.O. Egamberdiyev (Genius Journals, 2022)
This article describes the methods of using innovative educational technologies in the teaching of static concrete steel structures and their calculation methods
Keywords: truss; column; beam truss height; static definite truss